A new species of Gegeneophis Peters (Amphibia: Gymnophiona: Caeciliidae) from Maharashtra, India - Ravichandran, Masagoundanur S.; Gower, David J.; Wilkinson, Mark (Zootaxa, 2003)
A new species of caeciliid caecilian (Amphibia: Gymnophiona), Gegeneophis seshachari, is described from the Western Ghats of Maharashtra, India. Known only from the type specimen, this distinctive species differs from all other Indian caeciliids in lacking secondary annuli, and in possessing an unsegmented terminal shield. A rediagnosis of Gegeneophis is presented, and the caeciliid fauna of India is briefly discussed.